A fatal case of non- typhoidal salmonella pyogenic pericardial effusion in an immunocompetent adolescent - Yong, T.C.; Ahmad Kashfi, A.R. (2019)
Salmonella infection is common in tropical countries including Malaysia. It is invasive in immunocompromised and those of extreme ages. It typically presents with gastrointestinal symptoms such as diarrhea, abdominal pain or vomiting. Extra-intestinal manifestations are seen in 30% of salmonellosis cases. These atypical manifestation leads to difficulty and delay diagnosis thus poorer outcome. Pericardium involvement is estimated to be less than 2% of all cases and has mortality rate as high as 50%1 . As high as 70% of pericarditis cases were identified to be immunosuppressed2 ; these include chronic immunosuppressant usage, autoimmune disease, end stage renal failure, malignancy and etc. Herein, we report a fatal case of pyogenic pericardial effusion by Salmonella enteritidis in an immunocompetent adolescent.